Factors Influencing the Development of Agri-Food Exports in Small Open Emerging Economies (the example of the Republic of Moldova) - Alexandru STRATAN; Viorica LOPOTENCO; Liliana STAVER (Communications of International Proceedings, 2024)
The study of the factors influencing export growth is one of the essential areas of analysis for countries with small and open emerging economies in the context where export directly impacts GDP growth. This study aims to identify the factors that impact Agri-Food Exports in Small, Open, and Emerging Economies, mainly where the share of this group of goods is significant. The identified factors were divided into two groups: endogenous and exogenous. The practical part of the paper is based on the use of statistical research methods; in particular, a multiple regression model was built, which made it possible to evaluate the degree of influence of selected factors on Moldovan food product exports. The study results led to the repercussion that food inflation has the maximum impact on exports of agri-food products. At the same time, the conclusion was substantiated that the export of complex products has a more significant effect on economic growth, a fact that the government must be aware of to promote the export of industrially processed agri-food products. The methodological approach, as well as the direct results of the study, will be proposed for use in developing a strategy for developing the agri-food industry in the Republic of Moldova.
Keywords: Foreign trade; Small Open Emerging Economies; Agri-Food Exports; Food Inflation; Supply Chain.